(untitled) (Revista ADMPG, 2026)
This paper intended to provide an extended theoretical review about motivational theories, their role in the consumer behavior and, eventually, how metamotivation is initiated and its relation to hedonism. It’s visible to see the importance of Maslow (1943;1954;1967;1968;1970;1971) and Festinger (1957;1959) in the construction of this field of study, as well how big the perception that many segments have benefited from these researches is. The main conclusion of the article is the close relation between the metamotivations and the hedonism. As advises for further research, this study suggests academics to develop assignments covering Maslow’s D-values and B-values and to conduct researches regarding metahedonism.